PROBING BREAST CANCER THERAPEUTIC RESPONSES BY DNA CONTENT PROFILING - Gerashchenko, B. I.; Salmina, K.; Eglitis, J.; Erenpreisa, J. (International Journal of Medicine and Medical Research, 2019)
Background. Discrepancies in the interpretation of breast cancer therapeutic responses still exist mainly because of lack of standardized assessment criteria and methods. Objective. DNA content profiling of cells in the affected (cancerous) tissue before and after neoadjuvant chemotherapy (NAC) was applied to facilitate interpretation of therapeutic responses. Methods. Both diagnostic biopsy and operation materials representing the tissue of primary tumors surgically removed after NAC were subjected to DNA image cytometry. Polyploidy and aneuploidy in DNA histograms were evaluated with a prognostic Auer typing. Stemline DNA index (DI) values and percentages of cells that polyploidize (>4.5C) were also determined. Immunofluorescence staining was applied to evaluate proliferation (Ki-67), invasiveness (CD44), and self-renewal factors characteristic for stem cells (SOX2 and NANOG). Results. DNA content profiles of 12 breast cancer cases, of which 7 were triple-negative, revealed the features of tumor non-responsiveness to NAC in 7 cases, of which 5 were triple-negative. Among non-responsive cases there were 3 cases that showed enhanced polyploidization, suggesting the negative NAC effect. Near-triploid (DI=1.26-1.74) triple-negative cases were determined as most resistant to NAC. Cycling near-triploid cells may contribute to the excessive numbers of >4.5C cells. Polyploid cells were positive for Ki-67, CD44, SOX2, and NANOG. Conclusions. DNA content profiling data provide additional helpful information for interpreting therapeutic responses in NAC-treated breast cancers. Polyploid tumor cells possessing stem cell features can be induced by NAC. Because NAC effects in some cases may be unfavorable, the use of the further treatment strategy should be carefully considered.